2015
DOI: 10.1182/blood-2015-04-641696
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of an N-terminal fragment of von Willebrand factor in complex with factor VIII

Abstract: • The VWF D9 domains are flexibly tethered entities projecting outside antiparallel dimers of the VWF D3 domain. • Extensive interactionsbetween the VWF D9 domain and primarily the FVIII C1 domain mediate VWF-FVIII association.Binding to the von Willebrand factor (VWF) D9D3 domains protects factor VIII (FVIII) from rapid clearance. We performed single-particle electron microscopy (EM) analysis of negatively stained specimens to examine the architecture of D9D3 alone and in complex with FVIII. The D9D3 dimer ([… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 17 publications
6
45
1
Order By: Relevance
“…Ra Pharma is developing a , RA101495, that binds C5 with high affinity and allosterically inhibits convertase-mediated cleavage 93 . After receiving orphan drug designation for PNH, Ra advanced RA101495 to phase II trials using a once-daily subcutaneous self-administration scheme 94–96 .…”
Section: Complement-targeting Therapeuticsmentioning
confidence: 99%
“…Ra Pharma is developing a , RA101495, that binds C5 with high affinity and allosterically inhibits convertase-mediated cleavage 93 . After receiving orphan drug designation for PNH, Ra advanced RA101495 to phase II trials using a once-daily subcutaneous self-administration scheme 94–96 .…”
Section: Complement-targeting Therapeuticsmentioning
confidence: 99%
“…These studies have shown that the positively charged VWF-D9 surface is probably a binding site for FVIII-ap. 56,57 More detailed models are on the horizon, as the 3-dimensional structures suggest additional mutagenesis studies to identify specific residues that mediate FVIII-VWF binding.…”
Section: Fviii and Vwf Structural Biologymentioning
confidence: 99%
“…48,50 A VWF-D9 solution structure 55 ( Figure 3), as well as modeling based on single-particle electron microscopy of complexes formed by FVIII and VWF-D9D3 domains, 56,57 have allowed further analysis of the FVIII-VWF interface and of VWF-D9 mutations associated with reduced FVIII-VWF affinity and type 2N VWD. These studies have shown that the positively charged VWF-D9 surface is probably a binding site for FVIII-ap.…”
Section: Fviii and Vwf Structural Biologymentioning
confidence: 99%
“…20,21 Recently negativestain electron microscopy and hydrogen-deuterium exchange mass spectrometry (HDX MS) studies have revealed that VWF primarily interacts with the C1 domain of fVIII. 22,23 VWF binding protects fVIII from endocytosis 24 and the human-derived anti-C1 domain antibody KM33 inhibits fVIII uptake by human monocyte-derived dendritic cells (MDDCs). 25 Moreover, B-domain deleted (BDD) fVIII mutant constructs containing alanine substitutions at exposed C1 residues Arg2090, Lys2092, and Phe2093 alone or in combination showed reduced fVIII uptake by human MDDCs and macrophages and immunogenicity in fVIII knockout mice compared with wild-type BDD fVIII.…”
Section: Introductionmentioning
confidence: 99%